2004
DOI: 10.1016/j.ijdevneu.2003.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral response of macrophages and astrocytes to injury in the cerebral hemisphere of 6‐day‐old rat following prenatal gamma irradiation

Abstract: Wistar pregnant rats were exposed to a single 1.0 Gy dose of gamma rays on gestational days 13, 15, 17 or 19 (E13, E15, E17 and E19, respectively). When offsprings of the irradiated females became 6-day-old, they received a mechanical injury of the cerebral hemisphere. One or 2 days after the injury, [3H]thymidine was injected and the animals were perfused. Brain sections were processed for BSI-B4 isolectin histochemistry or immunohistochemistry for glial fibrillary acidic protein (GFAP) or S-100-beta protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
2
0
2
Order By: Relevance
“…The present study demonstrated that glial cell proliferation was bilaterally enhanced due to unilateral crush of the ON in a laminaspecific manner and this bilateral response is in accordance with previous studies on bilateral cellular changes that occur after unilateral injury of the ON (Bodeutsch et al, 1999;Setkowicz et al, 2004). Specifically, BrdU-positive cells were shown to express GFAP, characterizing astroglia (NFL ⁄ GCL) or Muller cells (INL), and OX-42, characterizing microglia (all layers).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study demonstrated that glial cell proliferation was bilaterally enhanced due to unilateral crush of the ON in a laminaspecific manner and this bilateral response is in accordance with previous studies on bilateral cellular changes that occur after unilateral injury of the ON (Bodeutsch et al, 1999;Setkowicz et al, 2004). Specifically, BrdU-positive cells were shown to express GFAP, characterizing astroglia (NFL ⁄ GCL) or Muller cells (INL), and OX-42, characterizing microglia (all layers).…”
Section: Discussionsupporting
confidence: 92%
“…The present study demonstrated that glial cell proliferation was bilaterally enhanced due to unilateral crush of the ON in a lamina‐specific manner and this bilateral response is in accordance with previous studies on bilateral cellular changes that occur after unilateral injury of the ON (Bodeutsch et al. , 1999; Setkowicz et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, one set of samples was directly cut with a cryotome and another was embedded in paraffin and then cut with a microtome. The paraffin samples were prepared according to the standard procedures described elsewhere [11]. All the rat brain samples were cut into 15 m thick sections and mounted on the ultralene foil.…”
Section: Methodsmentioning
confidence: 99%
“…Além disso, de acordo com dados da literatura, tanto a retina quanto o nervo óptico contralaterais ao olho lesionado são freqüentemente utilizados como controles em estudos in vivo e in vitro (BODEUTSCH et al, 1999). Contudo, de acordo com alguns autores, a utilização do hemisfério cerebral ipsolateral à enucleação ocular como controle, bem como a utilização da retina e do nervo óptico contralaterais ao olho lesionado como controles, deve ser cuidadosamente reconsiderada por diversas razões (BODEUTSCH et al, 1999;SETKOWICZ et al, 2004;PANAGIS et al, 2005). Existem indícios, por exemplo, da existência de pequenas projeções recíprocas entre as retinas (projeção retino-retinal) (MULLER e HOLLANDER, 1988), as quais poderiam justificar a proliferação bilateral de células da glia na retina após a secção unilateral do nervo óptico (PANAGIS et al, 2005).…”
Section: Discussionunclassified